Diminished Bone Strength Is Observed in Adult Women and Men Who Sustained a Mild Trauma Distal Forearm Fracture During Childhood. (October 2014) - Farr, Joshua N; Khosla, Sundeep; Achenbach, Sara J; Atkinson, Elizabeth J; Kirmani, Salman; McCready, Louise K; Melton, L Joseph; Amin, Shreyasee
ABSTRACT Children and adolescents who sustain a distal forearm fracture (DFF) owing to mild, but not moderate, trauma have reduced bone strength and cortical thinning at the distal radius and tibia. Whether these skeletal deficits track into adulthood is unknown. Therefore, we studied 75 women and 75 men (age range, 20 to 40 years) with a childhood (age <18 years) DFF and 150 sex‐matched controls with no history of fracture using high‐resolution peripheral quantitative computed tomography (HRpQCT) to examine bone strength (ie, failure load) by micro–finite element (µFE) analysis, as well as cortical and trabecular bone parameters at the distal radius and tibia. Level of trauma (mild versus moderate) was assigned using a validated classification scheme, blind to imaging results. When compared to sex‐matched, nonfracture controls, women and men with a mild trauma childhood DFF (eg, fall from standing height) had significant reductions in failure load (p < 0.05) of the distal radius, whereas women and men with a moderate trauma childhood DFF (eg, fall while riding a bicycle) had values similar to controls. Consistent findings were observed at the distal tibia. Furthermore, women and men with a mild trauma childhood DFF had significant deficits in distal radius cortical area (p < 0.05), and significantly lower dual‐energy X‐ray absorptiometry (DXA)‐derived bone density at the radius, hip, and total body regions compared to controls (all p < 0.05). By contrast, women and men with a moderate trauma childhood DFF had bone density, structure, and strength that did not differ significantly from controls. These findings in young adults are consistent with our observations in children/adolescents with DFF, and they suggest that a mild trauma childhood DFF may presage suboptimal peak bone density, structure, and strength in young adulthood. Children and adolescents who suffer mild trauma DFFs may need to be targeted for lifestyle interventions to help achieve improved skeletal health. © 2014 American Society for Bone and Mineral Research.